Methods to Estimate Source Zone Depletion of Fuel Releases by Groundwater Flow. Issue 1 (16th January 2018) - Mackay, Douglas; Paradis, Charles; Buscheck, Timothy; Daniels, Eric; Hathaway, Emily; de Sieyes, Nicholas; Rasa, Ehsan; Schmidt, Radomir; Peng, Juan
Abstract: We compare two methods for estimating the natural source zone depletion (NSZD) rate at fuel release sites that occurs by groundwater flow through the source zone due to dissolution and transport of biodegradation products. Dissolution is addressed identically in both methods. The "mass budget method", previously proposed and applied by others, estimates the petroleum hydrocarbon biodegradation rate based on dissolved electron acceptor delivery and dissolved biodegradation product removal by groundwater flow. The mass budget method relies on assumed stoichiometry for the degradation reactions and differences in concentrations of dissolved species (oxygen, nitrate, sulfate, reduced iron, reduced manganese, nonvolatile dissolved organic carbon, methane) at monitoring locations upgradient and downgradient of the source zone. We illustrate a refinement to account for degradation reactions associated with loss of reduced iron from solution. The "carbon budget method, " a simplification of approaches applied by others, addresses carbon‐containing species in solution or lost from solution (precipitated) and does not require assumptions about stoichiometry or information about electron acceptors. We apply both methods to a fuel release site with unusually detailed monitoring data and discuss applicability to more typical and less thoroughly monitored sites. The methods, as would typically be applied, yield similar results but have different constraints and uncertainties. Overall, we conclude that the carbon budget method has greater practical utility as it is simpler, requires fewer assumptions, accounts for most iron‐reducing reactions, and does not include CO2 that escapes from the saturated to the unsaturated zone. Abstract : Article Impact Statement : Refinement of methods for estimating the portion of natural source zone depletion that occurs by groundwater flow at fuel release sites.